Pengaruh Tingkat Risiko Pembiayaan Mudharabah Dan Musyarakah Terhadap Tingkat Profitabilitas Pada PT. Bank Syariah Indonesia, TBK KCP Stabat - Fahri Alfandi; Kamaliah R; Khairunnisa Khairunnisa (Yayasan Rahmat Islamiyah, 2022)
The purpose of this study is to find out empirically the influence of mudharabah and musyarakah financing risks on the level of profitability in PT. Bank Syariah Indonesia, Tbk KCP Stabat. The research approach used is a quantitative research approach with multiple linear regression analysis techniques supported by classical assumption tests (Normality Test, Multicolilinierity Test, Heteroskedasticity Test and Autocorrelation Test), then hypothesis test (statistical test t, statistical test f, and determination coefficient test). The results showed that partially or simultaneously the Mudharabah Financing Risk Level and the Musyarakah Financing Risk Level had a significant effect on Profitability in PT. Bank Syariah Indonesia, Tbk KCP Stabat. Mudharabah Financing Risk Level and Musyarakah Financing Risk Level affect Profitability Level (ROA) in PT. Bank Syariah Indonesia, Tbk KCP Stabat amounted to 90.3%, while the remaining 9.7% was influenced by other variables that were not present in this study. There is a negative or opposite relationship between research variables, meaning that if the risk level of mudharabah financing and the level of risk of musyarakah financing has increased then profitability (ROA) of PT. Bank Syariah Indonesia, Tbk KCP Stabat will experience a decline Conversely, if the risk level of mudharabah financing and the level of risk of musyarakah financing decreases then the profitability (ROA) of PT. Bank Syariah Indonesia, Tbk KCP Stabat will increase.